Understanding and Ameliorating Islamophobia - Moten, Abdul Rashid (Versita, Warsaw, 2012)

(untitled)
Though centuries old, Islamophobia has increased in intensity as it is extensively documented by surveys and reports published by various governmental and non-governmental organizations. This dislike towards Islam and Muslims is, due, amongst other factors, to an increasing number of Muslim citizens and asylum seekers in the West bent upon preserving their own identity giving rise to the perception of "us" versus "them." Such negative evaluations by the in-group may be due to the conflicting values, beliefs and the actual or perceived threat posed by Muslims. This is also attributed to the negative messages transmitted by the national media and the powerful elite. The strategy for countering Islamophobia must concentrate on "unlearning intolerance" by focusing on removing negative perceptions through education, reforming the media and reshaping the foreign policy of Western powers.